2008
DOI: 10.1890/06-1036.1
|View full text |Cite
|
Sign up to set email alerts
|

Controls of Spatial Variation in the Prevalence of Trematode Parasites Infecting a Marine Snail

Abstract: Geographic variability in abundance can be driven by multiple physical and biological factors operating at multiple scales. To understand the determinants of larval trematode prevalence within populations of the marine snail host Littorina littorea, we quantified many physical and biological variables at 28 New England intertidal sites. A hierarchical, mixed-effects model identified the abundance of gulls (the final hosts and dispersive agents of infective trematode stages) and snail size (a proxy for time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
136
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(140 citation statements)
references
References 63 publications
3
136
0
1
Order By: Relevance
“…In summary, the results obtained during this study revealed that the fluctuations in the community of larval digeneans of the snail H. australis can be detected at small spatial scale, using its natural distribution of 500 m. Given that local factors play an important role in determining the richness and abundance of larval digeneans in their snail host (Poulin and Mouritsen 2003;Byers et al 2008), therefore, differences in the spatio-temporal distribution of the community of larval digeneans in H. australis should not be attributed to the effect of only a limited number of factors. This study also highlights the importance of seasonality as a factor that must be considered in studies focused on the search for patterns structuring the communities of larval digeneans, at medium and large scales.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…In summary, the results obtained during this study revealed that the fluctuations in the community of larval digeneans of the snail H. australis can be detected at small spatial scale, using its natural distribution of 500 m. Given that local factors play an important role in determining the richness and abundance of larval digeneans in their snail host (Poulin and Mouritsen 2003;Byers et al 2008), therefore, differences in the spatio-temporal distribution of the community of larval digeneans in H. australis should not be attributed to the effect of only a limited number of factors. This study also highlights the importance of seasonality as a factor that must be considered in studies focused on the search for patterns structuring the communities of larval digeneans, at medium and large scales.…”
Section: Discussionmentioning
confidence: 63%
“…In the latest years, parasitological studies regarding different aspects of the host-parasite relationships have placed special emphasis on the spatial scale at which those relationships are examined (Poulin and Mouritsen 2003;Byers et al 2008). In general, infection processes are proximately driven by local factors (environmental conditions, resources or biotic interactions) which ultimately may be correlated over large regional scale (Byers et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The density of cockles and/or their shell length could contribute to spatial infection heterogeneity (Thieltges & Reise 2006, 2007, but in the present study dissected cockles displayed similar lengths and abundance everywhere. Among possible drivers of trematode distribution, the presence of birds (= definitive hosts) should be explored (Hechinger & Lafferty 2005, Byers et al 2008. Characteristics of the water body could also interfere with parasite transmission by miracidium or cercariae larvae and may explain heterogeneity at this scale.…”
Section: Discussionmentioning
confidence: 99%